Expert System Engineering to Diagnose Diseases Transmitted by Mosquito Bites Based on Web - Muhammad Arfan; Muhammad Syahid Pebriadi (Program Studi Teknik Komputer, 2025)
This research is software development aimed at engineering an expert system to diagnose diseases transmitted by mosquito bites based on the web. This system can provide an initial diagnosis of diseases transmitted by mosquito bites to patients based on symptoms they experience, without needing to directly consult an expert. The system development follows the Systems Development Life Cycle (SDLC) approach. SDLC itself in software engineering is a process for creating and developing systems, as well as models and methodologies used to develop systems. The method used in this expert system is forward chaining, where the tracking starts with a set of facts and then moves toward a conclusion. The system was developed using PHP programming language and MySQL as the software to store the data. The results show that the expert system provides consistent results and answers. Expert validation looked at two key aspects, resulting in scores of 91.50% and 90.95%. Both are categorized as